Evaluating and mapping the evidence that screening for diabetic foot disease meets the criteria for population-wide screening: a scoping review - Patricia M Kearney; Claire M Buckley; Sean F Dinneen; Caroline McIntosh; Paul Kavanagh; Lauren Connell; Jennifer A Pallin (BMJ Public Health)
Objective To evaluate and map the evidence around diabetes-related foot screening using the World Health Organisation screening principles, which set the gold standard for determining the appropriateness of introducing population-wide screening programmes internationally.Design A scoping review methodology in line with Arksey and O’Malley and the Joanna Briggs Institute.Data sources Medline (EBSCO), Scopus, ScienceDirect and EMBASE between 24 May 2022 and 12 July 2022. Reference lists of the selected studies, and ‘Google’ and ‘Google Scholar’ were also searched.Eligibility criteria Inclusion criteria were informed by the principles of screening. Articles, published in English since 2000, reporting on the impact of the diabetes-related foot ulcers, effectiveness of treatment available for those identified as being at risk, reliability of screening tests for screening for the at-risk foot and the effectiveness, cost-effectiveness, safety and ethics of diabetes-related foot screening programmes were included.Data extraction and synthesis Data were extracted by one reviewer, with data extraction headings relating to the principles of screening. A narrative synthesis approach was used to report the information from included studies.Results 46 articles were deemed eligible for inclusion. Diabetes-related foot ulcers are an important health condition associated with increased risk of mortality and poorer quality of life. However, there is insufficient evidence on the effectiveness of treatments to prevent disease development. Moreover, while consensus exists on what screening tools should be used to screen for risk factors, there is no agreement on threshold values. Finally, there is no available information on the potential budgetary, organisational or societal implications of a whole-population diabetes-related foot screening programme.Conclusion Existing evidence does not support the introduction of an organised population-wide screening programme in the context of World Health Organisation screening principles. Further research on treatment and management strategies for the at-risk foot and of whole-population screening programmes is required.